World Transportation Account, 1950-1953: Comment - Marx, Daniel; Gorter, Wytze (The Review of Economics and Statistics, 1958)
Daniel Marx, Jr., Wytze Gorter, World Transportation Account, 1950-1953: Comment, The Review of Economics and Statistics, Vol. 40, No. 1, Part 2. Problems in International Economics (Feb., 1958), pp. 42-44